Evil as privative: a McCabian defence - Scrutton, Anastasia Phillipa (International journal of philosophy and theology, 2024)
Not all theists who are members of the Abrahamic faiths will sign up to a particular metaphysics of evil: some may be sceptical theists, and others may be uninterested in metaphysical questions altogether. In this paper, I argue that theists in the Abrahamic faiths who are interested in metaphysics and who are not sceptical theists should endorse a privative account of evil. This is because a privative view of evil is the only metaphysic of evil that is compatible with the theism of the Abrahamic faiths. In order to persuade you of this, I will explain the religious importance of the privative view, and show how the three alternatives to the privative view that might initially appear compatible with theism are not, after all, compatible with the particular theism of the Abrahamic faiths. Privative views are often objected to on the basis that pain is an evil that does not seem like a privation. I will put forward one (non-exclusive) defence of the privative view of evil in response to this objection, drawing on the work of Herbert McCabe.